Out of Hospital Cardiac Arrest: A Case Report - Kenan Ljuhar (Albanian Journal of Trauma and Emergency Surgery, 2021)
Introduction: Sudden OHCA (Out of hospital cardiac arrest) is the third leading cause of death in industrialized nations. With more than 60% of cardiovascular deaths resulting from cardiac arrest, it remains the leading cause of death worldwide. Heart rhythms associated with cardiac arrest are divided into two groups: shockable rhythms (ventricular fibrillation/pulseless ventricular tachycardia (VF/pVT) and non-shockable rhythms (asystole and pulseless electrical activity (PEA)). VF is the most commonly identified arrhythmia in cardiac arrest patients. Urgent medical treatment includes cardiopulmonary resuscitation and early defibrillation.